Using Network Analysis Methodology to Increase the Efficiency of Main Streets for Emergency System Movement in Latakia City - اسعد شذى (Latakia University Journal -Engineering Sciences Series, 2021)
The emergency system is a system that applies rules and professions relating to science, technology, planning and management, in the event of extreme events. Speed management of street vehicles can be considered the backbone of this system, which can be divided into phases, from planning and preparedness to response (for accurate information on the exact location), Therefore, the need for detailed and accurate data on travel time and vehicle speed and delay increases rapidly, as analysis techniques and requirements change. Effective vehicle control can be achieved by integrating GPS traffic data, such as the speed of vehicles and the direction of traffic flow, to the GIS environment. This system provides the actual location and status of the vehicles in the network, according to a data set and graphics of the results shown in a map, gives a clearer picture of the traffic situation in each route in the network. This allows transport planners to choose the desired speed management method to improve the traffic system and assess the traffic pattern, to assess sufficiently well the speed management technique adopted. The main objective of this research was to provide enhanced network analysis of the street network in Latakia City based on travel time and vehicle speed. This makes it easier to determine the disability factor, the start time and the period of arrival at the nearest emergency hospital, for example, from the scene of the accident. This will help save the lives of those injured by reducing time, effort and resources, it also helps to find out how many hospitals can be found and travel trends (from accident to hospital or from hospital to accident), in the shortest possible time. The research also showed the importance of dealing with remote sensing techniques (positioning service) with geographic information systems (GIS), to build spatial data systems capable of effectively and efficiently managing the movement of emergency systems and any other transport or traffic system effectively and dynamically.